Spatial variability in sulphur isotope values of archaeological and modern cod (Gadus morhua). (9th September 2013) - Nehlich, Olaf; Barrett, James H.; Richards, Michael P.
<x xml:space="preserve">Abstract</x> RATIONALE This study presents the first sulphur isotope data of modern and archaeological cod (Gadus morhua) bone collagen, undertaken to identify large‐scale spatial variability of significance as both baseline values for studies of human diet and a potential variable in isotope‐based studies of fish trading. METHODS Collagen was extracted from modern and archaeological cod bones using a weak HCl solution and analysed for its sulphur isotopic composition by isotope ratio mass spectrometry (IRMS). RESULTS The archaeological cod have sulphur isotope values ranging from +9.1‰ to +18.2‰, whereas values for modern specimens range from +14.8‰ to +18.3‰. The modern data show values implying less freshwater influence, consistent with their offshore catch locations, but also corroborate some of the regional variability evident from the archaeological evidence. CONCLUSIONS The archaeological data have a large range of sulphur isotope values compared with the modern populations, probably indicating they were taken from a wide range of geographic locations, including both coastal and offshore locales. They show broad trends of regional difference that may relate to both the fish populations targeted (e.g. 'inshore' versus 'offshore') and the baseline values of the local ecosystem (e.g. degree of freshwater input from river systems). Copyright © 2013 John Wiley & Sons, Ltd.